2016
DOI: 10.15446/esrj.v20n3.55440
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Recent Global Geopotential Models for Strip Area Project in Turkey

Abstract: The aim of this study is to present the evaluations based on comparisons of geoid heights that are computed from several global geopotential models (GGMs) and the GNSS/levelling data. In this application framework, differences between geoid heights obtained by GGMs and GNSS/levelling were computed. Then, the availability of geoid heights calculated by GGMs for engineering applications were investigated. The Konya-Polatli (Ankara) Express Train Project as a strip area project was chosen as the study area. The l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…After the launch of the GOCE mission, GOCE based GGMs (2010-2012) in the whole of Turkey and in two local areas in the northwest of Turkey, namely Istanbul and Sakarya [46], in Bursa [47] in the western part of Turkey (37.30 N ⩽ ϕ ⩽ 40.44 N; 28.48 E ⩽ λ ⩽ 32.71 E) defining a total area of ~133.000 km 2 (350 km × 380 km) [48], and in the high-speed train route between Konya and Polatli (Ankara), which is 210 km long [49] were tested by combining GPS/levelling data. The results suggested that GOCE models show improvements over EGM2008.…”
Section: Study Areamentioning
confidence: 99%
“…After the launch of the GOCE mission, GOCE based GGMs (2010-2012) in the whole of Turkey and in two local areas in the northwest of Turkey, namely Istanbul and Sakarya [46], in Bursa [47] in the western part of Turkey (37.30 N ⩽ ϕ ⩽ 40.44 N; 28.48 E ⩽ λ ⩽ 32.71 E) defining a total area of ~133.000 km 2 (350 km × 380 km) [48], and in the high-speed train route between Konya and Polatli (Ankara), which is 210 km long [49] were tested by combining GPS/levelling data. The results suggested that GOCE models show improvements over EGM2008.…”
Section: Study Areamentioning
confidence: 99%
“…However, the effectiveness of these models in specific regions depends on their inherent quality and parameter settings [6]. Several studies by Doganalp [7], Nicacio et al [8], Goyal et al [9], Lee and Kwon [10], and Nyoka et al [11], have conducted evaluations in their respective fields to identify the most suitable model. Recent research by Wu et al [12] compared two gravity field models, XGM2016 and EGM2008, and found that the selection of the gravity field model significantly affects the accuracy of the geoid model within the study area.…”
Section: Introductionmentioning
confidence: 99%
“…The Earth's gravity field can be determined using satellite gravimeters. Various studies have been conducted using several satellite gravimeters, e.g., CHAMP (CHAllenging Minisatellite Payload), GRACE/GRACE-FO (Gravity Recovery And Climate Experiment/-Following On) and GOCE (Gravity field and steady-state Ocean Circulation Explorer), to produce geopotential models [3,12,23,22].…”
Section: Introductionmentioning
confidence: 99%